Determinação electromagnetically e estudo eletroquímico de bentazon e fenamifós utilizando eletrodos de diamante - Lima, Thays de Souza [UNIFESP] (2017)
This study aimed to develop an electroanalytical methodology for determination of bentazon (BTZ) and fenamiphos (FNP) and also the electrochemical study these pesticides by exhaustive electrolysis. The BTZ presented a single oxidation peak in +1.01 V vs Ag / AgCl, and theFNP presented a single oxidation peak at + 1.18 V vs Ag / AgCl, both with irreversible process characteristics and controlled by diffusion. To develop the methodology for quantification of pesticides has used square-wave voltammetry (SWV). The analytical curves were obtained in concentration range of 9.90x10-6 mol L-1 to 9.09x10-5 mol L-1. For the BTZ the detection limits (LOD) and quantification (LOQ) values were 3.00x10-6 mol L-1 and 9.90x10-6 mol L-1, respectively. For the FNP, the LOD and LOQ values were 1.50x10-6 mol L-1 and 4.98x10-6 mol L-1, respectively. The performance of the developed method was evaluated by recovery studies in natural water samples and showed recovery percentages of 98.0% and 109.2% for BTZ and FNP, respectively. Was also developed a method for the simultaneous and selective determination of BTZ and FNP, the best results were obtained using square wave voltammetry and chemometric methods with of a 33 factorial full design. With selected parameters an analytical curve was constructed in the concentration range of 9.90x10-6 mol L-1 to 9.09x10-5 mol L-1 for the mixture of BTZ and FNP. For BTZ the values of LOD and LOQ were 3.80 x 10-7 mol L-1 and 1.27 x 10-6 mol L-1, respectively. For FNP the LOD and LOQ values were 3.00 x10-6 mol L-1 and 9.90x10-6 mol L-1, respectively. The study of destructive oxidation on the boron-doped diamond (BDD) electrodes for pesticides was realized using electrolysis at controlled potential. The electrolysis monitoring with the square wave voltammetry techniques, absorption spectrometry in the UV- Visible, total organic carbon (TOC) analyzes, and liquid chromatography with mass detector (LC-MS). An initial concentration of the pesticides decay of the electrolysis course. The percentages initial decreasing around 50.7 % for BTZ and 55.0 % for FNP.